Correction to: Determining the cost-effectiveness requirements of an exoskeleton preventing second hip fractures using value of information - Stefania Manetti; Giuseppe Turchetti; Francesco Fusco (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.